Selected Robust Logistic Regression Specification for Classification of Multi‑dimensional Functional Data in Presence of Outlier - Krzyśko, Mirosław; Smaga, Łukasz (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
In this paper, the binary classification problem of multi‑dimensional functional data is considered. To solve this problem a regression technique based on functional logistic regression model is used. This model is re‑expressed as a particular logistic regression model by using the basis expansions of functional coefficients and explanatory variables. Based on re‑expressed model, a classification rule is proposed. To handle with outlying observations, robust methods of estimation of unknown parameters are also considered. Numerical experiments suggest that the proposed methods may behave satisfactory in practice.